Elżbieta Maria WALERIAN, Ph.D., D.Sc. - MEISSNER, Mirosław (Archives of Acoustics, 2014)
Elżbieta M. Walerian, Ph.D., D.Sc., a retired employee of the Institute of Fundamental Technologica Research of the Polish Academy of Sciences (IPPT PAN), passed away after a serious illness, on the 26th December 2013. She was one of the scientific leaders in the Section of Environmental Acoustics of IPPT PAN and her career, educational and organizational activities were inseparably linked with the acoustics.